Conservation education in Aotearoa-New Zealand: a values perspective. (30th June 2022) - Birdsall, Sally; Kelly, Tim
Abstract: Throughout the world, Aotearoa-New Zealand is recognised for its extraordinary biodiversity. However, many species that make up this distinctive biodiversity are under threat of extinction due to human impacts, such as the ill-considered introduction of particular animals. Many New Zealanders participate in the protection and restoration of their environment, which involves the lethal control of these introduced animals. Primary school children (5–13 years old) engage in conservation education as part of their learning, which aims to develop their abilities to take informed action to protect and restore our environment, sometimes including lethal control of introduced animals. Recently, concerns have been raised that children learning about the lethal control of introduced animals does not align with the values that should be explored and encouraged according to Aotearoa-New Zealand's national curriculum. We argue that conservation education, including learning about the lethal control of introduced animals, encourages children to explore and encourage these values, namely valuing the diversity in their heritages, ecological sustainability, participation for the common good, equity, innovation, and respect for others.